Ply Parameters Optimization and Strength Reliability Analysis of Wind Turbine Blade. Issue 3 (January 2021) - Yu, Zelin; Sun, Pengwen
Abstract: As the critical component of capturing wind energy, the performance and reliability of blade are directly related to the safe, stable operation and service life of wind turbines. The performance of the blade is mainly determined by the ply parameters, so it has important valueto study the optimization method of ply parameters and the analysis method of strength reliability of wind turbine blade.In this paper, the load of a 1.5MW wind turbine bladeunder the DLC1.5g-2 working condition is calculated and its finite element model is established. Combined with engineering practice, the investigation range of ply parameters is determined, the test scheme is designed by using the mixed level uniform experiment method, and the blade strength is analyzed. Based on the polynomial regression analysis method and simulation results, the quadratic mathematical model between the ply parameters and the Tsai-Wu failure factors is established, and the range of ply parameters is optimized by mean value analysis method and interaction analysis method. On this basis, the ply parameters are regarded as random variables, and the structural performance function of blade failure is constructed. The reliability of the blade is predicted by the first-order second-moment method. The results show that the blade is reliable in the range of optimized ply parameters. The work provides the method and technical support for the laminate structure design and optimization of wind turbine blade.